Academic self-efficacy and teacher social support as predictors of academic flow mathematics among senior high school students in Jambi City - Ramadhanti, Auliya; Fathiyah, Kartika Nur; Putra, Rahman Pranovri (UIN Maulana Malik Ibrahim Malang, 2025)
Many senior high school students face challenges in situations that require mathematical skills, often resulting in low interest and discomfort in learning mathematics. This study aims to examine the influence of academic self-efficacy and teacher social support on academic flow in the context of mathematics learning among high school students. Employing a quantitative ex-post facto design, the study involved 420 students selected through a probability sampling method using a multistage cluster random sampling technique, due to the large population size. Data were collected using modified instruments: the Flow Perceptions Questionnaire (FPQ), the Academic Self-Efficacy Scale, and the Foreign Language Teacher Support Scale (FLTSS). Data analysis was conducted using prerequisite tests and multiple regression analysis. The findings revealed that both academic self-efficacy and teacher social support significantly predict students’ experience of academic flow in mathematics learning. Students who possess strong confidence in their academic capabilities and receive substantial social support from teachers are more likely to engage positively in mathematics learning through the experience of academic flow. These results highlight the importance of fostering students’ academic self-efficacy and enhancing the quality of teacher support to optimize academic flow in mathematics education. KEY WORDS: academic flow; academic self-efficacy; teacher social support; mathematics; high school student